Decision Analysis of Dividend Distribution versus Share Buyback in Shareholder Value Strategy - Syaiful, Syaiful (Advances in Management & Financial Reporting, 2025)
Purpose: This study analyzes the decision-making process behind dividend distribution and share buybacks, focusing on how companies balance short-term financial goals with long-term shareholder value maximization. The research addresses how internal factors, such as cash flow stability and profitability, and external factors, such as market conditions and investor expectations, influence these financial strategies. Research Design and Methodology: This study uses a qualitative systematic literature review (SLR) to synthesize findings from recent studies on corporate financial strategies. The research consolidates insights into the underlying mechanisms, strategic motivations, and implications of dividend and buyback policies by reviewing and analyzing relevant literature from reputable academic sources. Findings and Discussion: The findings reveal that dividend distribution fosters investor trust by providing consistent returns, signaling financial stability, and enhancing corporate reputation. Conversely, share buybacks offer companies greater flexibility, particularly in volatile markets, by reducing the number of outstanding shares and signaling stock undervaluation. The discussion highlights that both strategies serve as mechanisms to mitigate agency conflicts, aligning management actions with shareholder expectations. However, buybacks must be transparent to avoid negative perceptions of financial manipulation. Implications: The study underscores the practical importance of aligning capital return policies with investor preferences and corporate growth objectives. Managers are encouraged to communicate transparently and adopt balanced financial policies supporting shareholder returns and sustainable reinvestment. Policymakers may also benefit from understanding how regulatory changes impact corporate payout decisions, providing a basis for more effective corporate governance frameworks.